Mathematics In The Era Of The Abbasid Dynasty: Al-Khawarizmi’s Contribution To The Development Of Modern Mathematical Thought In Baghdad 780-850 CE - Kamila Ainur Ridho; Rijalul Fikri; Ellya Roza (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2026)
The development of knowledge during the Abbasid Caliphate marked the emergence of the Islamic Golden Age, supported by political and institutional backing for intellectual activities. In this context, mathematics flourished through processes of translation, synthesis, and innovation, reaching its peak in the works of Al-Khawarizmi. This study examines the historical dynamics of the development of mathematics during the Abbasid Caliphate, focusing its analysis on Al-Khawarizmi’s intellectual contributions. The research employs the historical method with a descriptive-analytical approach through literature-based data collection techniques. The research procedures include heuristics, interpretation, and synthesis of various sources discussing the development of algebra, arithmetic, and algorithms during that period. The findings indicate that Al-Khawarizmi made significant contributions to the systematic formulation of algebraic concepts, the introduction of the Hindu-Arabic numeral system, and the development of algorithmic methods that later became foundational to modern computer science. With the support of the Abbasid caliphs, particularly through the House of Wisdom in Baghdad, mathematics advanced rapidly and had a profound impact on Islamic civilization as well as the wider world.